Aerodynamic characteristics of two-dimensional sharp-edged objects in tandem arrangement - Gnatowska, R. (Archives of Mechanics, 2008)
The present analysis addresses the problem of the aerodynamic loads of two prismatic bodies in tandem arrangement. Two identical square cross-section prismatic bodies arranged in tandem are considered and represent a two-dimensional configuration. The program of the study consists of parallel wind-tunnel experiments and numerical simulation performed with the use of a phase-averaged form of k-ε turbulence model in RNG version. The simulations revealed a strong dependence between the interference of the wake flow around the system of sharp-edged bluff-bodies, the vorticity structure of the separation region, mean position of the reattachment point, phase-averaged velocity field and skin friction variability. The general aim was to establish a direct link between the flow around bluff bodies, local time-resolved quantities like skin friction and surface pressure, and near-wake behaviour behind the square cylinders in tandem array. In particular, it was found that periodical flow disturbances bring about a rapid growth of surface pressure and wall shear stress fluctuations.